(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article derives from the Master’s thesis Diving in the Dark: The Theater is [in] the Encounter with the Other in the World, held at the Fine Arts School of the Minas Gerais Federal University in Performing Arts. For this research, an artistic residency based on contemporary theater practices took place in three female prisons. This work derived from the premise that writing and sharing personal letters could serve as the epigraph for a theatrical event. The work revealed the power of the performing arts in workshops with female prisoners.